Structural and Electron-hopping Studies of Pr and Nd substituted La2/3Ba1/3MnO3 Manganites - Abdullah, Huda; Shaari, Abdul Halim (Trans Tech Publications, 2009)
The significance of substituting concentrations of Pr and Nd at La-sites, in La0.67Ba0.33MnO3 perovskite compounds, for the structural and electrical properties have been studied. Polycrystalline samples (La1-x Prx)0.67Ba0.33MnO3 and (La1-x Ndx)0.67Ba0.33MnO3 with x = 0.00, 0.167, 0.333, 0.5, 0.667, 0.833 and 1.0 were synthesized via conventional solid-state reaction in the bulk. All of the samples were calcined at 900oC for 12 hours, pelletized and sintered at 1300oC for 24 hours and investigated. In this paper the structural patterns and microstructural properties of bulk samples have been investigated via x-ray diffractometry (XRD) and scanning electron microscopy (SEM). XRD patterns show that these systems are single-phase, with orthorhombic distorted perovskite structures. The electrical property, Tp, was determined by using standard four-point probe resistivity measurements in the temperature range of 20 K to 300 K. The result shows that Pr and Nd dopants shift the value of TP to a lower temperature. When the temperature is above Tp, T > Tp, the variation of the electrical resistance was found to follow the an Arhenius-type law, ρ = ρo exp (-Ea/KBT). It was used to calculate the activation energy of every sample. The resistivity curves show semiconducting behavior of all samples above their Tp.